Development and implementation of kintung-based learning media in elementary music education - Mahendra, Benny; Milyartini, Rita; Masunah, Juju (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
The limited availability of contextual and culture-based music learning media in elementary schools restricts students’ understanding of musical concepts and diminishes engagement with local cultural values. This study aims to develop and implement Kintung-based music learning media by utilizing the traditional bamboo musical instrument of the Banjar community to enhance students’ musical skills and cultural appreciation. The research adopted a Research and Development (R&D) design using the ADDIE model, with qualitative techniques embedded in each stage. During the Analysis phase, data were collected through interviews, observations, and documentation of Kintung practices in community and school settings involving musicians, art teachers, and elementary school sudents. The Design and Development stages involved selecting appropriate bamboo materials, cutting and shaping resonant tubes, tuning instruments to the diatonic scale, and preparing instructional materials aligned with learning objectives. The Implementation stage consisted of learning activities structured into preparation, presentation, practice, and performance, through which students learned instrument-playing techniques, rhythmic patterns, and traditional Banjar songs such as Ampar-Ampar Pisang and Ampat Si Ampat Lima. Evaluation results indicate that the media effectively improved students’ technical performance, rhythmic accuracy, ecological awareness, and appreciation of local culture. This study concludes that Kintung-based, music learning media provides a culturally grounded and pedagogically relevant innovation for integrating traditional music into elementary education, supporting students’ musical skill development, and contributing to the preservation of local cultural identity.